Identification of a novel circulating recombinant form (CRF3301B) disseminating widely among various risk populations in Kuala Lumpur, Malaysia - Tee, K.K.; Li, X.J.; Nohtomi, K.; Ng, K.P.; Kamarulzaman, Adeeba; Takebe, Y. (Lippincott, Williams & Wilkins, 2006)
A molecular epidemiological investigation was conducted among various risk populations (n = 184) in Kuala Lumpur, Malaysia, in 2003 to 2005, on the basis of nucleotide sequences of protease and reverse transcriptase regions. In addition to circulating HIV-1 strains, including CRF01AE (57.1), subtype B (20.1), and subtype C (0.5), we detected a candidate with a new circulating recombinant form (CRF). We determined four near-full-length nucleotide sequences with identical subtype structure from epidemiologically unlinked individuals of different risk and ethnic groups. In this chimera, two short subtype B segments were inserted into the gag-RT region in a backbone of CRF01AE. The recombinant structure was distinct from previously identified CRF1501B in Thailand. In agreement with the current HIV nomenclature system, this constitutes a novel CRF (CRF3301B). The overall prevalence of CRF3301B is 19.0 (35/184). Although the prevalence of CRF3301B is particularly high among injecting drug users (42.0, 21/50), it is also detected in a substantial proportion of homo-/bisexual males (18.8, 3/16) and heterosexuals (9.8, 9/92). Moreover, unique recombinant forms composed of CRF01AE and subtype B that have a significant structural relationship with CRF3301B were detected in 1.6 (3/184) of study subjects, suggesting an ongoing recombination process in Malaysia. This new CRF seems to be bridging viral transmission between different risk populations in this country.